Multi-objective composite part mechanical optimization enhanced by a Process Estimator. (January 2015) - Eck, B.; Comas-Cardona, S.; Binetruy, C.; Aufrere, C.
Abstract: In this study the multi-objective optimization of a fiber reinforced composite part will be presented. Additionally to the weight and the mechanical properties, its manufacturability with the Resin Transfer Molding process is considered during the optimization. For the last mentioned, a new CPU-time efficient method, called Process Estimator, was developed. Based on the local material parameters it allows to calculate the filling times of complex and fine meshed parts with varying permeabilities and porosities in some seconds to minutes. The rapidity of the method will be illustrated with the help of three example parts. These examples demonstrate the importance of the process consideration during a mechanical design optimization.